2013
DOI: 10.1530/jme-13-0229
|View full text |Cite
|
Sign up to set email alerts
|

AGEs induce caspase-mediated apoptosis of rat BMSCs via TNFα production and oxidative stress

Abstract: Diabetic humans and animals exhibit lower bone mass and healing, resulting from diminished bone formation. We have recently reported that type 1 diabetic rats have fewer bone marrow osteoprogenitor cells, and since the formation of advanced glycation end products (AGEs) in bone increases in diabetes, we explored possible mechanisms involved in AGE-induced apoptosis of rat bone marrow stromal cells (BMSCs). BMSCs isolated from 4-month-old rats were exposed to 10-400 mg/ml AGE-BSA for 16 h and apoptosis was quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 70 publications
1
53
0
2
Order By: Relevance
“…Many apoptosisrelated signaling pathways participate in this process, including activation of MAPKs and increasing activation of caspase-3, -8, and -9 (Alikhani et al 2007, Weinberg et al 2014. Consistent with previous studies, apoptosis was also induced in AGEs-treated osteoblastic MC3T3-E1 cells in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many apoptosisrelated signaling pathways participate in this process, including activation of MAPKs and increasing activation of caspase-3, -8, and -9 (Alikhani et al 2007, Weinberg et al 2014. Consistent with previous studies, apoptosis was also induced in AGEs-treated osteoblastic MC3T3-E1 cells in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Human and animal experiments have shown that AGEs accumulate dramatically in bone tissue during diabetes, and are associated with bone cell dysfunction as well as bone tissue fragility (Santana et al 2003, Yoon et al 2004, Hein et al 2006, Momma et al 2012, Fajardo et al 2014, Hofbauer et al 2016. Several studies have demonstrated that AGEs can induce apoptosis in bone cells through MAPK, p38, caspase-8, and caspase-9 signaling pathways; however, this apoptotic response cannot fully explain the susceptibility of diabetic patients with normal BMD to fracture (Alikhani et al 2007, Weinberg et al 2014, Tanaka et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Predominantly, changes in ROS and hypoxia from neighboring cells in the presence of excessive glucose alter juxtacrine and paracrine signaling to the stem cells. 77,78 Moreover, diabetes causes an influx of inflammatory cells and stimulates adipocyte production, altering the stem cell microenvironment. 79 These molecular changes are addressed in this section.…”
Section: Molecular Pathways That Underlie Stem Cell Dysfunction Durinmentioning
confidence: 99%
“…Pretreatment of hyperglycemia-exposed bone marrow MSCs with pirfenidone, a tumor necrosis factor-a blocker, and N-acetyl-L-cysteine can counter ROS-induced inflammation and progenitor apoptosis through modulation of AGEs. 78 Taken together, preclinical data suggest that enriched autologous progenitor cell subsets preconditioned in vitro to metabolically withstand a high-glucose, high-ROS environment are a promising approach for treating diabetic complications. In the event where sufficient numbers of critical autologous progenitor subsets cannot be obtained, readily available banked allogenic progenitors from adult bone marrow, adipose tissue, or blood, or from umbilical cord blood or placenta, might serve as alternative sources of cell-based therapy.…”
Section: Progenitor Cells and Diabetesmentioning
confidence: 99%
“…AGE treatment promotes a significant release of activators of caspase-3, including Cyt c (cytochrome c) and ROS (reactive oxygen species) from mitochondria to cytoplasmic compartment, which then activates caspase-3 (Weinberg et al, 2014). To elucidate the apoptosis induced by Glu-BSA and etomidate treatment, we ana- lyzed the Cyt c release, activated caspase 3 level and the lysis of poly-ADP-ribose polymerase (PARP) by caspase 3 with western blot assay.…”
Section: Etomidate and Glu-bsa Synergistically Upregulated Apoptosis-mentioning
confidence: 99%